Bringing Product Management to Your Organization - LeMay, Matt (O'Reilly Media, Inc., 2017)
Successful product management (PM) is often a critical step towards launching products that find success in the market. But why do so many organizations struggle to create their own thriving PM practices? Who are the right people to bring on as product managers? How can you set up to succeed? And should you change the way you currently work to accommodate them? This short class provides strategies for successfully bringing PM into your organization. Learn how to identify your PM needs, hire the right people, and set them up for success Discover the best ways to identify internal and external candidates for PM roles Survey the most effective practices for interviewing PM candidates Understand how to guide your organization toward successful PM practices Matt Lemay is cofounder of Constellate Data, a business intelligence research, consulting, and training company based in NYC. Matt has developed and led product management and data strategy workshops for companies like GE, American Express, Pfizer, McCann, and Johnson & Johnson. Previously, Matt worked as the Senior Product Manager for the music startup Songza (acquired by Google) and as the Head of Consumer Product at Bitly. He is the author of the O'Reilly title Product Management in Practice: A Real-World Guide to the Key Connective Role of the 21st Century.